EXPERIENCES OF HIV/AIDS PATIENTS UNDERGOING ANTIRETROVIRAL THERAPY (ARV) AT THE CST POLYCLINIC PSYCHIATRIC HOSPITAL OF BANGKONG RIVER PONTIANAK CITY - Ratnasari, Anggita Diah Hadi (Universitas Tanjungpura, 2022)
Background: HIV/AIDS is a disease that attacks the human immune system. ARV therapy is a physical therapy given to people infected with HIV to reduce the amount of HIV virus in the body and prevent opportunistic infections with various complications. Method: descriptive qualitative research with in-depth interviews. The approach used is the phenomenological approach. The number of participants was 7 PLWHA undergoing ARV Therapy at CST Polyclinic at Sungai Bangkong Psychiatric Hospital in PontianakResults: Participants were infected with HIV/AIDS from infected partners (husband/wife), injecting addicts, homosexuals and promiscuity. Side effects of therapy experienced include rash, nausea/vomiting, increased liver function, dizziness, fever. Stigma was experienced by some of the participants because of the lack of exposure to information related to HIV/AIDS in the family environment. All participants applied adaptive coping mechanisms which were influenced by the support from their families and the surrounding environment. Conclusion: the experience of HIV/AIDS patients undergoing ARV therapy in the Sungai Bangkong CST Polyclinic is different because each person has their own uniqueness, both in terms of causal factors, side effects of therapy, stigma and discrimination that are experienced, as well as forms of family support patient.Keywords: HIV/AIDS, Antiretroviral Therapy, ARV Side Effects,Reference: 57 (2007-2021)